2022
DOI: 10.1038/s41467-022-28065-6
|View full text |Cite
|
Sign up to set email alerts
|

Overlooked and widespread pennate diatom-diazotroph symbioses in the sea

Abstract: Persistent nitrogen depletion in sunlit open ocean waters provides a favorable ecological niche for nitrogen-fixing (diazotrophic) cyanobacteria, some of which associate symbiotically with eukaryotic algae. All known marine examples of these symbioses have involved either centric diatom or haptophyte hosts. We report here the discovery and characterization of two distinct marine pennate diatom-diazotroph symbioses, which until now had only been observed in freshwater environments. Rhopalodiaceae diatoms Epithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 74 publications
(85 reference statements)
4
31
1
Order By: Relevance
“…The apparent utilization of nitrate by diatoms could explain the observed decline in nitrate seawater concentrations, which was faster with increasing eutrophic conditions. Previous findings in the literature showed that members of the Raphid-pennate family could display a widespread symbiosis with marine diazotroph organisms under persistent nitrate depletion (Schvarcz et al, 2022). Shifts in dissolved silicate concentrations in our dust-treated microcosms could be related to this diatom assemblage, but also to other identified siliceous protists (such as radiolarians and silicoflagellates) and potentially Synechococcus cyanobacteria (Baines et al, 2012).…”
Section: Cell Abundances Structure and Composition Of Microbial Commu...supporting
confidence: 53%
“…The apparent utilization of nitrate by diatoms could explain the observed decline in nitrate seawater concentrations, which was faster with increasing eutrophic conditions. Previous findings in the literature showed that members of the Raphid-pennate family could display a widespread symbiosis with marine diazotroph organisms under persistent nitrate depletion (Schvarcz et al, 2022). Shifts in dissolved silicate concentrations in our dust-treated microcosms could be related to this diatom assemblage, but also to other identified siliceous protists (such as radiolarians and silicoflagellates) and potentially Synechococcus cyanobacteria (Baines et al, 2012).…”
Section: Cell Abundances Structure and Composition Of Microbial Commu...supporting
confidence: 53%
“…For context, all-dark N 2 fixation as a percent of the natural-light N 2 fixation in the NCD-dominant South Pacific Gyre ranges from 28% to over 100% 45 and 63% to over 100% in a temperate estuary 46 .The comparison of all-dark to natural-light community N 2 fixation rates could be used to infer photosynthesis-independent N 2 fixation. However, cyanobacteria that fix N 2 in the dark such as Crocosphaera , and Cyanothece 47 as well as the endosymbiont (spherical body) of the diatom Epithemia pelagica that fixes N 2 in the light and dark alike 48 are all present in our samples according to nifH gene sequences ( Crocosphaera: 0–39%, Cyanothece and Epithemia pelagica spherical body <1%, Supplementary Fig. 1 ) and make all-dark N 2 fixation rates unreliable for estimating N 2 fixation by NCDs.…”
Section: Resultsmentioning
confidence: 99%
“…A metagenomic study also showed evidence of cyanobacterial particle association based on size fractionated samples 50 . Additionally, cyanobacterial nifH sequences were found on particles at 4000 m ( Crocosphaera , Richelia and Epithemia pelagica -spherical body ) 48 , 67 yet the cyanobacterial diazotrophic activity on particles is unknown. As such, the cyanobacterial abundances could be due to typically C-fixing cyanobacteria using heterotrophic C acquisition while attached to particles and would therefore be categorized as a NCD in this study.…”
Section: Resultsmentioning
confidence: 99%
“…However, not all diazotrophs can be counted using traditional microscopy—this includes UCYN‐A, undescribed cyanobacterial diazotrophs (new species continue to be discovered; Schvarcz et al. 2022), and NCDs (Moisander et al. 2017).…”
Section: Figmentioning
confidence: 99%
“…Since empirical nifH:cell is not 1:1, direct cell counts may be preferable when possible and practical. However, not all diazotrophs can be counted using traditional microscopy-this includes UCYN-A, undescribed cyanobacterial diazotrophs (new species continue to be discovered; Schvarcz et al 2022), and NCDs (Moisander et al 2017). A recent report of non-N 2fixing Trichodesmium (Delmont 2021) also highlights the need for nifH-based methods to complement cell abundance data when the genetic potential for N 2 fixation is in question.…”
mentioning
confidence: 99%